Dealcoholized silicone sealant stable in storage and capable of being rapidly cured and preparation method of dealcoholized silicone sealant

By preparing the cyclodextrin metal frame material and alkoxy end capping 107 glue and other components, the problems of slow curing speed and poor storage stability of dealcohol type silicone sealant are solved, and stable storage and fast curing are achieved Effect.

CN119463798AActive Publication Date: 2025-02-18GUANGZHOU BAIYUN CHEM IND +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411646444.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-02-18
Estimated Expiration
2044-11-18

AI Technical Summary

Technical Problem

Dealcoholized silicone sealant has problems of slow curing speed and poor storage stability, which limits its further promotion in the construction and industrial fields.

Method used

By preparing the combination of cyclodextrin metal frame material and alkoxy end capped 107 glue and other components, specific dehydration blending and mixing reaction conditions are used to prepare a dehydration-stable storage and fast curable dehydration silicone sealant.

Benefits of technology

The storage stability and deep curing speed of the dehydrogenated silicone sealant are significantly improved, and its performance in industrial applications is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005139817740000011
    Figure BDA0005139817740000011
  • Figure BDA0005139817740000031
    Figure BDA0005139817740000031
  • Figure BDA0005139817740000041
    Figure BDA0005139817740000041
Patent Text Reader

Abstract

The invention relates to a dealcoholized silicone sealant which is stable to store and can be quickly cured and a preparation method of the dealcoholized silicone sealant. The dealcoholized silicone sealant is prepared from the following raw materials in parts by mass: 100 parts of alkoxy terminated 107 glue; 20 to 50 parts of dimethyl silicone oil; 30 to 100 parts of a cyclodextrin metal framework material; 100 to 200 parts of an inorganic filler; 0.5 to 1.5 parts of a cross-linking agent; 0.2 to 1.0 part of a coupling agent; and 2-8 parts of a titanate catalyst. The cyclodextrin is prepared into a cyclodextrin metal frame material, the cyclodextrin metal frame material is used for preparing the dealcoholized silicone sealant, the storage stability of the dealcoholized silicone sealant can be remarkably improved, meanwhile, the cyclodextrin metal frame material has high affinity to water, the permeation rate of water vapor in the sealant can be increased, and the dealcoholized silicone sealant has the advantages of being high in stability and good in sealing performance. Therefore, the deep curing speed of the dealcoholized silicone sealant can be obviously improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of sealants, and in particular relates to a storage-stable, rapidly curable dealcoholized silicone sealant and a preparation method thereof. Background Art

[0002] Silicone sealants are widely used in construction and industrial fields due to their good weather resistance and high and low temperature resistance. Among them, dealcoholized silicone sealants are more environmentally friendly because they release small alcohol molecules during the curing process, have no irritating odor, are non-corrosive to metal substrates, and have a wide range of substrate bonding. Therefore, the demand for them has been rising in recent years.

[0003] However, the dealcoholized silicone sealant has the disadvantages of slow curing speed, and its curing performance will be significantly attenuated during storage, and its storage stability is poor, which restricts its further promotion. Therefore, it is necessary to prepare a dealcoholized silicone sealant that is stable in storage and can be cured quickly. Summary of the invention

[0004] Based on this, the object of the present invention is to provide a storage-stable and rapidly curable dealcoholized silicone sealant.

[0005] The technical solutions for achieving the above-mentioned purpose include the following.

[0006] In one aspect, the present invention provides a dealcoholized silicone sealant, which is prepared from raw materials including the following components in parts by mass:

[0007]

[0008] The preparation method of the cyclodextrin metal frame material comprises the following steps:

[0009] (1) filtering the aqueous solution containing cyclodextrin and potassium hydroxide into methanol and allowing to stand at 40° C. to 60° C. for 4 h to 8 h;

[0010] (2) adding hexadecyltrimethylammonium bromide to the mixed solution obtained in step (1), stirring evenly, and standing at 20° C.-30° C. for 8 h-24 h to obtain the cyclodextrin metal framework material.

[0011] On the other hand, the present invention provides a method for preparing the dealcoholized silicone sealant, comprising the following steps:

[0012] The alkoxy-terminated 107 glue, dimethyl silicone oil, cyclodextrin metal frame material and inorganic filler are dehydrated and blended at a temperature of 90°C to 130°C and a vacuum degree of -0.08MPa to -0.099MPa for 60min to 180min, cooled to 40°C to 50°C, and the cross-linking agent, coupling agent and catalyst are added. The mixture is mixed and reacted for 40min to 120min at a vacuum degree of -0.08 to -0.099MPa and a stirring speed of 100rpm to 800rpm to obtain the dealcoholized silicone sealant.

[0013] The present invention has the following beneficial effects:

[0014] The present invention prepares cyclodextrin into a cyclodextrin metal frame material, and then prepares a dealcoholized silicone sealant by combining the cyclodextrin with components such as alkoxy-terminated 107 glue, which can significantly improve the storage stability of the dealcoholized silicone sealant. At the same time, the cyclodextrin metal frame material has a strong affinity for water, which can increase the permeation rate of water vapor inside the glue, thereby significantly increasing the deep curing speed of the dealcoholized silicone sealant. The dealcoholized silicone sealant of the present invention has excellent storage stability and deep curing speed under the coordination of various components.

[0015] By optimizing the specific selection and ratio of each preparation raw material, the storage stability and deep curing speed of the obtained alcohol-type silicone sealant are further improved.

[0016] The preparation methods of the cyclodextrin metal frame material and the dealcoholized silicone sealant provided by the invention are simple and conducive to industrial production. DETAILED DESCRIPTION

[0017] In order to facilitate the understanding of the present invention, the present invention will be described more fully below. The present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive.

[0018] The experimental methods in the following examples without specifying specific conditions are usually carried out under conventional conditions or conditions recommended by the manufacturers. The various commonly used chemical reagents used in the examples are all commercially available products.

[0019] Unless otherwise defined, all technical and scientific terms used in the present invention have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. The terms used in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used in the present invention includes any and all combinations of one or more of the related listed items.

[0020] In addition, as used in the present invention, the term "or" is an inclusive "or" symbol and is equivalent to the term "and / or", unless the context clearly dictates otherwise. The term "based on" is not exclusive and allows for being based on other factors not described, unless the context clearly dictates otherwise. In addition, throughout the specification, the meanings of "a", "an", and "the" include plural referents. The meaning of "in..." includes "in..." and "on...".

[0021] Some of the embodiments involve a dealcoholized silicone sealant, which is prepared from raw materials including the following components in parts by mass:

[0022]

[0023] In some preferred embodiments, the dealcoholized silicone sealant is prepared from raw materials including the following components, in parts by mass:

[0024]

[0025]

[0026] In some preferred embodiments, the dealcoholized silicone sealant is prepared from raw materials including the following components, in parts by mass:

[0027]

[0028] In some preferred embodiments, the method for preparing the cyclodextrin metal framework material comprises the following steps:

[0029] (1) filtering the aqueous solution containing cyclodextrin and potassium hydroxide into methanol and allowing to stand at 40° C. to 60° C. for 4 h to 8 h;

[0030] (2) adding hexadecyltrimethylammonium bromide to the mixed solution obtained in step (1), stirring evenly, and standing at 20° C.-30° C. for 8 h-24 h to obtain the cyclodextrin metal framework material.

[0031] In some preferred embodiments, the cyclodextrin is one or more of α-cyclodextrin, β-cyclodextrin and γ-cyclodextrin.

[0032] In some preferred embodiments, the cyclodextrin is γ-cyclodextrin.

[0033] In some preferred embodiments, the mass ratio of cyclodextrin, potassium hydroxide and hexadecyltrimethylammonium bromide is 1g: 0.2g-0.5g: 0.2mg-0.6mg.

[0034] In some preferred embodiments, the mass ratio of cyclodextrin, potassium hydroxide and hexadecyltrimethylammonium bromide is 1g: 0.3g-0.4g: 0.3mg-0.5mg.

[0035] In some preferred embodiments, the concentration of cyclodextrin in the aqueous solution is 25 g / L to 40 g / L.

[0036] In some preferred embodiments, the concentration of cyclodextrin in the aqueous solution is 30 g / L to 35 g / L.

[0037] In some preferred embodiments, the volume ratio of methanol to water is 1:0.8-1.2.

[0038] In some preferred embodiments, the method for preparing the cyclodextrin metal framework material comprises the following steps:

[0039] (1) dissolving the cyclodextrin and potassium hydroxide in water, filtering the resulting solution into a reaction kettle filled with methanol, and standing at 40° C.-60° C. for 4 h-8 h;

[0040] (2) adding the hexadecyltrimethylammonium bromide to the mixed solution obtained in step (1), stirring evenly, standing at 20° C.-30° C. for 8 h-24 h, filtering, washing, and drying to obtain the cyclodextrin metal framework material;

[0041] In some preferred embodiments, in step (1), the mixture is allowed to stand at 45° C.-55° C. for 4 h-6 h.

[0042] In some preferred embodiments, in step (2), the mixture is allowed to stand at 25°C-30°C for 12h-16h.

[0043] In some preferred embodiments, the drying is performed under vacuum conditions at 40°C-60°C.

[0044] In some preferred embodiments, the alkoxy-terminated 107 gum is at least one of methyl dimethoxy-terminated 107 gum, methyl diethoxy-terminated 107 gum, vinyl dimethoxy-terminated 107 gum, vinyl diethoxy-terminated 107 gum, trimethoxy-terminated 107 gum and triethoxy-terminated 107 gum.

[0045] In some preferred embodiments, the viscosity of the alkoxy-terminated 107 glue at 25° C. is 10000 mPa·s to 100000 mPa·s.

[0046] In some preferred embodiments, the viscosity of the alkoxy-terminated 107 glue at 25° C. is 15000 mPa·s to 25000 mPa·s.

[0047] In some preferred embodiments, the viscosity of the dimethyl silicone oil at 25° C. is 100 mPa·s to 500 mPa·s.

[0048] In some preferred embodiments, the viscosity of the dimethyl silicone oil at 25° C. is 300 mPa·s to 400 mPa·s.

[0049] In some preferred embodiments, the inorganic filler is at least one of nano-active calcium carbonate, light calcium carbonate and heavy calcium carbonate.

[0050] In some preferred embodiments, the crosslinking agent is at least one of methyltrimethoxysilane, methyltriethoxysilane, propyltrimethoxysilane, octyltrimethoxysilane and phenyltrimethoxysilane.

[0051] In some preferred embodiments, the coupling agent is at least one of γ-aminopropyltrimethoxysilane, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane, γ-glycidoxypropyltrimethoxysilane, γ-mercaptopropyltrimethoxysilane and 3-isocyanatepropyltrimethoxysilane.

[0052] In some preferred embodiments, the titanate catalyst is selected from at least one of tetraisopropyl titanate, tetrabutyl titanate, diisopropyl di(ethyl acetoacetate) titanate, dibutoxybis(ethyl acetoacetate) titanate and diisobutyl di(ethyl acetoacetate) titanate.

[0053] Some of the embodiments involve a method for preparing the dealcoholized silicone sealant of the present invention, comprising the following steps:

[0054] The alkoxy-terminated 107 glue, dimethyl silicone oil, cyclodextrin metal frame material and inorganic filler are dehydrated and blended at a temperature of 90°C to 130°C and a vacuum degree of -0.08MPa to -0.099MPa for 60min to 180min, cooled to 40°C to 50°C, and the cross-linking agent, coupling agent and catalyst are added. The mixture is mixed and reacted for 40min to 120min at a vacuum degree of -0.08 to -0.099MPa and a stirring speed of 100rpm to 800rpm to obtain the dealcoholized silicone sealant.

[0055] The present invention is further described in detail below with reference to specific embodiments.

[0056] In the following examples, unless otherwise specified, "parts" refer to parts by weight.

[0057] In the following examples, unless otherwise specified, the viscosity mentioned refers to the viscosity tested at 25°C.

[0058] Example 1

[0059] 162g of γ-cyclodextrin and 56g of potassium hydroxide were dissolved in 5.0L of water, and then the solution was filtered through an organic filter membrane into a reactor containing 4.5L of methanol. After standing and diffusing at 50°C for 5h, 66.5mg of hexadecyltrimethylammonium bromide was added, stirred evenly, and stood at 25°C for 12h. The solution was filtered, and the obtained crystals were washed twice with 1.5L of methanol, and then dried under vacuum at 50°C to obtain a cyclodextrin metal framework material (γ-CD-MOF).

[0060] 100 parts of methyl dimethoxy-terminated 107 glue with a viscosity of 20000 mPa·s, 40 parts of dimethyl silicone oil with a viscosity of 350 mPa·s, 80 parts of γ-CD-MOF, and 160 parts of nano-activated calcium carbonate were dehydrated and blended at a temperature of 110°C and a vacuum degree of -0.098 MPa for 120 minutes. After being fully cooled to 45°C, 0.8 parts of methyltrimethoxysilane, 0.5 parts of N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane and 4 parts of di(ethyl acetoacetate) diisopropyl titanate were added, and the mixture was mixed and reacted for 80 minutes at a vacuum degree of -0.098 MPa and a stirring speed of 300 rpm to obtain a storage-stable, fast-curing dealcoholized silicone sealant composition.

[0061] Example 2

[0062] 100 g of α-cyclodextrin and 35 g of potassium hydroxide were dissolved in 3.0 L of water, and then the solution was filtered through an organic filter membrane into a reactor containing 3.0 L of methanol. After standing and diffusing at 60 ° C for 4 hours, 40 mg of hexadecyltrimethylammonium bromide was added, stirred evenly, and stood at 30 ° C for 18 hours. The above solution was filtered, and the obtained crystals were washed twice with 1.0 L of methanol, and then dried under vacuum conditions at 60 ° C to obtain a cyclodextrin metal framework material (α-CD-MOF).

[0063] 100 parts of methyl diethoxy-terminated 107 glue with a viscosity of 50000 mPa·s, 20 parts of dimethyl silicone oil with a viscosity of 500 mPa·s, 50 parts of α-CD-MOF, and 100 parts of light calcium carbonate were dehydrated and blended at a temperature of 130°C and a vacuum degree of -0.090 MPa for 60 minutes. After being fully cooled to 50°C, 0.5 parts of methyl triethoxy silane, 1.0 parts of γ-glycidyloxypropyl trimethoxy silane and 8 parts of dibutoxy bis(ethyl acetoacetate) titanate were added, and the mixture was mixed and reacted for 120 minutes at a vacuum degree of -0.085 MPa and a stirring speed of 100 rpm to obtain a storage-stable, fast-curing dealcoholized silicone sealant composition.

[0064] Example 3

[0065] 200 g of β-cyclodextrin and 70 g of potassium hydroxide were dissolved in 6.0 L of water, and then the solution was filtered through an organic filter membrane into a reactor containing 5.0 L of methanol. After standing and diffusing at 40 ° C for 8 hours, 85 mg of hexadecyltrimethylammonium bromide was added, stirred evenly, and stood at 25 ° C for 24 hours. The above solution was filtered, and the obtained crystals were washed twice with 2.0 L of methanol, and then dried under vacuum conditions at 40 ° C to obtain a cyclodextrin metal framework material (β-CD-MOF).

[0066] 100 parts of trimethoxy-terminated 107 glue with a viscosity of 100000 mPa·s, 50 parts of dimethyl silicone oil with a viscosity of 100 mPa·s, 30 parts of β-CD-MOF, and 200 parts of heavy calcium carbonate were dehydrated and blended at a temperature of 90°C and a vacuum degree of -0.080 MPa for 180 minutes. After being fully cooled to 40°C, 1.5 parts of propyltrimethoxysilane, 0.2 parts of γ-aminopropyltrimethoxysilane and 2 parts of diisobutyl di(ethyl acetoacetate) titanate were added, and the mixture was mixed and reacted for 40 minutes at a vacuum degree of -0.095 MPa and a stirring speed of 800 rpm to obtain a storage-stable, fast-curing dealcoholized silicone sealant composition.

[0067] Example 4

[0068] The difference between this embodiment and embodiment 1 is that α-cyclodextrin is used instead of γ-cyclodextrin, and the other preparation raw materials and reaction conditions of the cyclodextrin metal frame material and the dealcoholized silicone sealant composition are the same as those in embodiment 1.

[0069] 162g of α-cyclodextrin and 56g of potassium hydroxide were dissolved in 5.0L of water, and then the solution was filtered through an organic filter membrane into a reactor containing 4.5L of methanol. After standing and diffusing at 50°C for 5h, 66.5mg of hexadecyltrimethylammonium bromide was added, stirred evenly, and stood at 25°C for 12h. The solution was filtered, and the obtained crystals were washed twice with 1.5L of methanol, and then dried under vacuum at 50°C to obtain a cyclodextrin metal framework material (α-CD-MOF).

[0070] 100 parts of methyl dimethoxy-terminated 107 glue with a viscosity of 20000 mPa·s, 40 parts of dimethyl silicone oil with a viscosity of 350 mPa·s, 80 parts of α-CD-MOF, and 160 parts of nano-activated calcium carbonate were dehydrated and blended at a temperature of 110°C and a vacuum degree of -0.098 MPa for 120 minutes. After being fully cooled to 45°C, 0.8 parts of methyltrimethoxysilane, 0.5 parts of N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane and 4 parts of di(ethyl acetoacetate) diisopropyl titanate were added, and the mixture was mixed and reacted at a vacuum degree of -0.098 MPa and a stirring speed of 300 rpm for 80 minutes to obtain a storage-stable, fast-curing dealcoholized silicone sealant composition.

[0071] Example 5

[0072] The difference between this embodiment and embodiment 1 is that β-cyclodextrin is used instead of γ-cyclodextrin, and the other preparation raw materials and reaction conditions of the cyclodextrin metal frame material and the dealcoholized silicone sealant composition are the same as those in embodiment 1.

[0073] 162g of β-cyclodextrin and 56g of potassium hydroxide were dissolved in 5.0L of water, and then the solution was filtered through an organic filter membrane into a reactor containing 4.5L of methanol. After standing and diffusing at 50°C for 5h, 66.5mg of hexadecyltrimethylammonium bromide was added, stirred evenly, and stood at 25°C for 12h. The solution was filtered, and the obtained crystals were washed twice with 1.5L of methanol, and then dried under vacuum at 50°C to obtain a cyclodextrin metal framework material (β-CD-MOF).

[0074] 100 parts of methyl dimethoxy-terminated 107 glue with a viscosity of 20000 mPa·s, 40 parts of dimethyl silicone oil with a viscosity of 350 mPa·s, 80 parts of β-CD-MOF, and 160 parts of nano-activated calcium carbonate were dehydrated and blended at a temperature of 110°C and a vacuum degree of -0.098 MPa for 120 minutes. After being fully cooled to 45°C, 0.8 parts of methyltrimethoxysilane, 0.5 parts of N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane and 4 parts of di(ethyl acetoacetate) diisopropyl titanate were added, and the mixture was mixed and reacted at a vacuum degree of -0.098 MPa and a stirring speed of 300 rpm for 80 minutes to obtain a storage-stable, fast-curing dealcoholized silicone sealant composition.

[0075] Comparative Example 1

[0076] The difference between this comparative example and Example 1 is that no cyclodextrin metal frame material is added to the dealcoholized silicone sealant composition, and other preparation raw materials and reaction conditions of the dealcoholized silicone sealant composition are the same as those in Example 1.

[0077] 100 parts of methyl dimethoxy-terminated 107 glue with a viscosity of 20000 mPa·s, 40 parts of dimethyl silicone oil with a viscosity of 350 mPa·s, and 160 parts of nano-activated calcium carbonate were dehydrated and blended at a temperature of 110°C and a vacuum degree of -0.098 MPa for 120 minutes. After being fully cooled to 45°C, 0.8 parts of methyl trimethoxy silane, 0.5 parts of N-(β-aminoethyl)-γ-aminopropyl trimethoxy silane and 4 parts of diisopropyl di(ethyl acetoacetate) titanate were added, and the mixture was mixed and reacted at a vacuum degree of -0.098 MPa and a stirring speed of 300 rpm for 80 minutes to obtain a dealcoholized silicone sealant composition.

[0078] Comparative Example 2

[0079] The difference between this comparative example and Example 1 is that γ-cyclodextrin is used in equal amount to replace γ-CD-MOF, and other preparation raw materials and reaction conditions of the dealcoholized silicone sealant composition are the same as those in Example 1.

[0080] 100 parts of methyl dimethoxy-terminated 107 glue with a viscosity of 20000 mPa·s, 40 parts of dimethyl silicone oil with a viscosity of 350 mPa·s, 80 parts of γ-cyclodextrin, and 160 parts of nano-activated calcium carbonate were dehydrated and blended at a temperature of 110°C and a vacuum degree of -0.098 MPa for 120 minutes. After being fully cooled to 45°C, 0.8 parts of methyltrimethoxysilane, 0.5 parts of N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane and 4 parts of di(ethyl acetoacetate) diisopropyl titanate were added, and the mixture was mixed and reacted at a vacuum degree of -0.098 MPa and a stirring speed of 300 rpm for 80 minutes to obtain a dealcoholized silicone sealant composition.

[0081] The following performance tests were performed on the dealcoholized silicone sealant compositions prepared in Examples 1-5 and Comparative Examples 1-2:

[0082] 1. Surface drying time: Tested according to method B of GB / T 13477.5-2002 "Test methods for building sealing materials Part 5: Determination of surface drying time".

[0083] 2. 24h curing depth (mm) test: Take two square glass pieces with a side length of 50mm, clean the surface with ethanol and dry it, then put a glue ball on one of the glass pieces, press the other glass piece on the glue ball, make the upper and lower glass pieces parallel, and control the distance between them to be 6mm. Use a scraper to scrape away the overflowing glue around the edges of the two parallel glass pieces and ensure that the surface of the glue is flat. After curing the specimen in an environment of 23℃ and 50%RH for 24h, cut the glue along the parallel surface. After removing the uncured glue, measure the thickness of the cured glue around the edge of the specimen, and take the average value, which is the 24h curing depth value.

[0084] The test results are shown in Table 1: It can be seen from Comparative Example 1 and Example 1 that the addition of cyclodextrin metal frame material can significantly improve the storage stability of the dealcoholized silicone sealant and increase the deep curing speed of the dealcoholized silicone sealant.

[0085] From the comparison between Comparative Example 2 and Comparative Example 1 and Example 1, it can be seen that cyclodextrin can also improve the storage stability of the dealcoholized silicone sealant and increase the deep curing speed to a certain extent, but its effect is far worse than the cyclodextrin metal frame material of the present invention. The dealcoholized silicone sealant added with cyclodextrin metal frame material has better storage stability and higher deep curing speed.

[0086] From the comparison of Examples 1, 4 and 5, it can be seen that the effect of γ-CD-MOF on improving the storage stability of dealcoholized silicone sealant is better than that of β-CD-MOF and α-CD-MOF.

[0087] Table 1

[0088]

[0089]

[0090] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A dealcoholized silicone sealant, characterized in that: The product is prepared from the following raw materials in parts by mass:

2. The dealcoholized silicone sealant according to claim 1, characterized in that: The product is prepared from the following raw materials in parts by mass:

3. The dealcoholized silicone sealant according to claim 1 or 2, characterized in that: The preparation method of the cyclodextrin metal frame material comprises the following steps: (1) filtering the aqueous solution containing cyclodextrin and potassium hydroxide into methanol and allowing to stand at 40° C. to 60° C. for 4 h to 8 h; (2) adding hexadecyltrimethylammonium bromide to the mixed solution obtained in step (1), stirring evenly, and standing at 20° C.-30° C. for 8 h-24 h to obtain the cyclodextrin metal framework material.

4. The dealcoholized silicone sealant according to claim 3, characterized in that: The cyclodextrin is one or more of α-cyclodextrin, β-cyclodextrin and γ-cyclodextrin, preferably γ-cyclodextrin.

5. The dealcoholized silicone sealant according to claim 3, characterized in that: The mass ratio of the cyclodextrin, potassium hydroxide and hexadecyltrimethylammonium bromide is 1g: 0.2g-0.5g: 0.2mg-0.6mg, preferably 1g: 0.3g-0.4g: 0.3mg-0.5mg.

6. The dealcoholized silicone sealant according to claim 3, characterized in that: The concentration of the cyclodextrin in the aqueous solution is 25 g / L to 40 g / L, preferably 30 g / L to 35 g / L; and / or the volume ratio of the methanol to water is 1:0.8-1.

2.

7. The dealcoholized silicone sealant according to claim 3, characterized in that: The preparation method of the cyclodextrin metal frame material comprises the following steps: (1) dissolving the cyclodextrin and potassium hydroxide in water, filtering the resulting solution into a reaction kettle filled with methanol, and standing at 40° C.-60° C. for 4 h-8 h; (2) adding the hexadecyltrimethylammonium bromide to the mixed solution obtained in step (1), stirring evenly, standing at 20° C.-30° C. for 8 h-24 h, filtering, washing, and drying to obtain the cyclodextrin metal framework material; In step (1), the mixture is preferably allowed to stand at 45°C-55°C for 4h-6h; In step (2), the mixture is preferably allowed to stand at 25°C-30°C for 12h-16h; Preferably, the drying is carried out under vacuum conditions at 40°C-60°C.

8. The dealcoholized silicone sealant according to claim 1 or 2, characterized in that: The alkoxy-terminated 107 glue is at least one of methyl dimethoxy-terminated 107 glue, methyl diethoxy-terminated 107 glue, vinyl dimethoxy-terminated 107 glue, vinyl diethoxy-terminated 107 glue, trimethoxy-terminated 107 glue and triethoxy-terminated 107 glue; Preferably, the viscosity of the alkoxy-terminated 107 glue at 25° C. is 10000 mPa·s to 100000 mPa·s, more preferably 15000 mPa·s to 25000 mPa·s.

9. The dealcoholized silicone sealant according to claim 1 or 2, characterized in that: The viscosity of the dimethyl silicone oil at 25° C. is 100 mPa·s to 500 mPa·s, preferably 300 mPa·s to 400 mPa·s; and / or, The inorganic filler is at least one of nano-active calcium carbonate, light calcium carbonate and heavy calcium carbonate; and / or, The crosslinking agent is at least one of methyltrimethoxysilane, methyltriethoxysilane, propyltrimethoxysilane, octyltrimethoxysilane and phenyltrimethoxysilane; and / or, The coupling agent is at least one of γ-aminopropyltrimethoxysilane, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane, γ-glycidoxypropyltrimethoxysilane, γ-mercaptopropyltrimethoxysilane and 3-isocyanatepropyltrimethoxysilane; and / or, The titanate catalyst is selected from at least one of tetraisopropyl titanate, tetrabutyl titanate, diisopropyl di(ethyl acetoacetate) titanate, dibutoxy di(ethyl acetoacetate) titanate and diisobutyl di(ethyl acetoacetate) titanate.

10. A method for preparing the dealcoholized silicone sealant according to any one of claims 1 to 9, characterized in that: The steps include: The alkoxy-terminated 107 glue, dimethyl silicone oil, cyclodextrin metal frame material and inorganic filler are dehydrated and blended at a temperature of 90°C to 130°C and a vacuum degree of -0.08MPa to -0.099MPa for 60min to 180min, cooled to 40°C to 50°C, and the cross-linking agent, coupling agent and catalyst are added. The mixture is mixed and reacted for 40min to 120min at a vacuum degree of -0.08 to -0.099MPa and a stirring speed of 100rpm to 800rpm to obtain the dealcoholized silicone sealant.

Citation Information

Patent Citations

  • Rapidly and deeply curable dealcoholized single-component silicone sealant and preparation method thereof

    CN111892906A

  • Preparation method and application of terpinen-4-ol loaded gamma-cyclodextrin metal organic framework membrane

    CN115109322A

  • Method for growing cyclodextrin metal organic framework crystal on polymer matrix, CD-MOFs compound and application of CD-MOFs compound

    CN117659419A

  • Environment-friendly long-acting mildew-proof silicone sealant and preparation method thereof

    CN117683510A